Expression and purification of Suid Herpesvirus-1 glycoprotein E in the baculovirus system and its use to diagnose Aujeszky’s disease in infected pigs - Serena, Maria Soledad (2013)
Suid Herpesvirus 1 (SHV-1) is the etiological agent of Aujeszky’s disease (AD), which affects swine herds worldwide and causes substantial economic losses due to animal mortality and lost productivity. In order to eradicate SHV-1, vaccination programs using viruses lacking the gene encoding glycoprotein E (gE) are ongoing in several countries. These eradication programs have generated a currently unmet demand for affordable and sensitive tests that can detect SHV-1 infection, yet distinguish between infected and vaccinated pigs. To meet this demand, we used the baculovirus-insect cell system to produce immunologically authentic full-length recombinant gE protein for use in a serum ELISA assay. As previous efforts to clone the gE gene had failed due to its extremely high GC-content (75% average), we used betaine as a PCR enhancer to facilitate amplification of the entire gE gene from the Argentinian CL15 strain of SHV-1. The cloned gE gene was expressed at high levels in recombinant baculovirus-infected insect cells and reacted strongly with sera from SHV-1 infected pigs. We used the recombinant gE protein to develop a local indirect ELISA test with sensitivity and specificity comparable to currently available commercial tests. Thus, recombinant gE produced in baculovirus-infected insect cells is a viable source of antigen for the detection of SHV-1 in ELISA tests. We also provide evidence supporting a potential application of this recombinant form of gE as a SHV-1 subunit vaccine.